PROTEROZOIC MOUNTAIN BUILDING IN PENINSULAR INDIA: AN ANALYSIS BASED PRIMARILY ON ALKALINE ROCK DISTRIBUTION - Leelanandam C.; Burke K.; Ashwal L.D.; Webb S.J. (My University, 2006)
Peninsular India was assembled into a continental block c. 3 million km2 in area as a result of collisions throughout the length of a 4000 km long S-shaped mountain belt that was first recognized from the continuity of strike of highly deformed Proterozoic granulites and gneisses. More recently the recognition of a variety of tectonic indicators, including occurrences of ophiolitic slivers, Andean-margin type rocks, a collisional rift and a foreland basin, as well as many structural and isotopic age studies have helped to clarify the history of this Great Indian Proterozoic Fold Belt. We here complement those studies by considering the occurrence of deformed alkaline rocks and carbonatites (DARCs) in the Great Indian Proterozoic Fold Belt. One aim of this study is to test the recently published idea that DARCs result from the deformation of alkaline rocks and carbonatites (ARCs) originally intruded into intra-continental rifts and preserved on rifted continental margins. The suggestion is that ARCs from those margins are transformed into DARCs during continental, or arc-continental, collisions. If that idea is valid, DARCs lie on rifted continental margins and on coincident younger suture zones; they occur in places where ancient oceans have both opened and closed. Locating sutures within mountain belts has often proved difficult and has sometimes been controversial. If the new idea is valid, DARC distributions may help to reduce controversy. This paper concentrates on the Eastern Ghats Mobile Belt of Andhra Pradesh and Orissa, where alkaline rock occurrences are best known. Less complete information from Kerala, Tamil Nadu, Karnataka, West Bengal, Bihar and Rajasthan has enabled us to define a line of 47 unevenly distributed DARCs with individual outcrop lengths of between 30 m and 30 km that extends along the full 4000 km length of the Great Indian Proterozoic Fold Belt. Ocean opening along the rifted margins of the Archaean cratons of Peninsular India may have begun by c. 2.0 Ga and convergent plate margin phenomena have left records within the Great Indian Proterozoic Fold Belt and on the neighbouring cratons starting at c. 1.8 Ga. Final continental collisions were over by 0.55 Ga, perhaps having been completed at c. 0.75 Ga or at c. 1 Ga. Opening of an ocean at the Himalayan margin of India by c. 0.55 Ga removed an unknown length of the Great Indian Proterozoic Fold Belt. In the southernmost part of the Indian peninsula, a line of DARCs, interpreted here as marking a Great Indian Proterozoic Fold Belt suture, can be traced within the Southern Granulite Terrain almost to the Achankovil-Tenmala shear zone, which is interpreted as a strike-slip fault that also formed at c. 0.55 Ga.
Keywords: INDIA; ALKALINE ROCKS; CARBONATITES; CONTINENTAL RIFTS; CONTINENTAL COLLISIONS; SUTURE; Докембрий::Протерозой; Precambrian::Proterozoic